Nurturing sexual orientation among children - Zulkefly, Nor Sheereen (Universiti Putra Malaysia, 2019)
Sexual orientation other than heterosexuality is believed to be unnatural, sinful and dangerous in a country like Malaysia that is steadfast in religion and culture. Children sexual orientation has subsequently been a sensitive, challenging, and frightening topic for parents. Past studies have documented the role of nature and nurture in the development of social orientation. Although preliminary studies have found genetic to be a significant factor, it was inconclusive if it was the only factor in determining sexual orientation. Hence, this paper will highlight the role of parents in nurturing sexual orientation of children. Despite lack of studies in local and Western context, the few studies available indicated that a secure attachment bond between parent and child is essential for healthy psychosexual and identity development. Additionally, this paper highlights the importance of communication, unconditional love and support between parent and child throughout the developmental stages leading to adulthood. Furthermore, this paper will briefly discuss possible treatment options for children with sexual orientation issues and its impact on children psychological health and well-being. This paper will conclude with suggestions on future research to further understand the development of sexual orientation in children.